2011
DOI: 10.1071/an10186
|View full text |Cite
|
Sign up to set email alerts
|

Blood proteins of red deer introduced to Patagonia: genetic origins and variability

Abstract: A small group of European red deer (Cervus elaphus elaphus) was introduced into the foothills of the Andes in Patagonia in the early 1920s. This species adapted well to the habitat and climatic conditions in the area and presently may number over 100 000 animals. Several indices commonly used to evaluate the fitness of a species in its environment indicate that red deer thrive under very favourable conditions in Patagonia; for example, body size, antler development, reproductive rates, herd health, and longevi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
4
1
Order By: Relevance
“…From our recordings of the vocalisations produced by red deer stags (Cervus elaphus) in the study area of Nahuel Huapi, the reproductive calls were found to be similar to their native European counterparts in that we could identify the three main vocalisations as for the deer of the Island of Rhum in Scotland McComb 2003a, 2003b). Although some red deer from Nahuel Haupi have a genetic component from wapiti (Cervus elaphus canadiensis), with the superoxide dismutase allele typical for wapiti found to occur in 11% of animals in the present study population (Flueck and Smith-Flueck 2011), these deer have roars typical of red deer. The bugle, which is the rut vocalisation characteristic of wapiti (Feighny et al 2006), was never apparent in any of the vocalisations recorded.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…From our recordings of the vocalisations produced by red deer stags (Cervus elaphus) in the study area of Nahuel Huapi, the reproductive calls were found to be similar to their native European counterparts in that we could identify the three main vocalisations as for the deer of the Island of Rhum in Scotland McComb 2003a, 2003b). Although some red deer from Nahuel Haupi have a genetic component from wapiti (Cervus elaphus canadiensis), with the superoxide dismutase allele typical for wapiti found to occur in 11% of animals in the present study population (Flueck and Smith-Flueck 2011), these deer have roars typical of red deer. The bugle, which is the rut vocalisation characteristic of wapiti (Feighny et al 2006), was never apparent in any of the vocalisations recorded.…”
Section: Discussioncontrasting
confidence: 53%
“…The results of the present study have shown that an exotic European red deer population separated from Europe for over a century has vocalisation patterns almost indistinguishable from those of the native red deer. The fact that the F0s observed in the Patagonian red deer are somewhat higher than those observed in the red deer from Rhum (Reby and McComb 2003a) may indicate a genetic influence of wapiti on the roars, given that Patagonian red deer do have some wapiti genetic markers (Flueck and Smith-Flueck 2011). Playback experiments in captive females of red deer have demonstrated that sometimes females preferred mating calls of heterospecific males (Cervus nippon) to those of conspecific males (Cervus elaphus), in spite of the acoustic and spectrographic differences between the two (Wyman et al 2011).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…data). FMD was tested for by SENASA in deer from Site B (n = 41) in 1994-1995, to allow export of the tissue as part of a genetic study (Flueck and Smith-Flueck 2011a); all samples were negative. Among an additional 393 specimens collected for reproductive and physical-condition studies, the only notable pathological finding was a suspected case of mycobacterial infection from Site D. We submitted fresh tissue from this specimen to INTA, but no cultivation was done.…”
Section: Resultsmentioning
confidence: 99%
“…The topography is primarily mountainous, with most features formed by glacial and volcanic processes. The study sites are between 900-m and 1800-m elevation and represent grasslands, or ecotones between forests and grasslands (details in Flueck and Smith-Flueck 2011a). We evaluated females older than 1 year, shot and collected randomly between 1991 and 2009, and radio-collared deer that died naturally between 2001 and 2009.…”
Section: Methodsmentioning
confidence: 99%